Women involvement in dispute resolution at the community level from Islamic perspective: a case study in Malaysia and Pakistan - Ambaras Khan, Hanna; Mehmood, Muhammad Ifzal; Abdul Hak, Nora (2016)
Islam has prescribed Sulh or amicable settlement or mediation as the default dispute resolution method in resolving the dispute. Women may also contribute in maintaining the harmony in the society as they play key roles in the administration of social problems in every society. In many Muslims majority or Islamic countries, there are different tools used to resolve the dispute at the community level. In Pakistan, there is a parallel judicial system for dispute resolution named Jirga. The members of Jirga are the elders of the community selected by the people. Unfortunately, until today there is no female representation in community mediation through Jirga. Women are barred from consultation in disputes resolution at community level, which have created discrimination against woman. On the other hand, in Malaysia, the Department of National Unity and Integration has trained women to be community mediators in resolving neighbourhood disputes at the community level. This paper discusses the disputes resolution in Islam and women participation, roles of female involvement in resolving neighbourhood disputes at community level in Malaysia and Pakistan. Subsequently, this paper suggests some amendment and recommendation to Jirga system to allow women participation in building peace in the society as permitted by Islam.